Basing information on comprehensive, critically appraised, and up-to-date syntheses of the scientific evidence: a quality dimension of the International Patient Decision Aid Standards - Montori, Victor M (BioMed Central, 2013)
BACKGROUND: Patients and clinicians expect patient decision aids to be based on the best available research evidence. Since 2005, this expectation has translated into a quality dimension of the International Patient Decision Aid Standards. METHODS: We reviewed the 2005 standards and the available literature on the evidence base of decision aids as well as searched for parallel activities in which evidence is brought to bear to inform clinical decisions. In conducting this work, we noted emerging and research issues that require attention and may inform this quality dimension in the future. RESULTS: This dimension requires patient decision aids to be based on research evidence about the relevant options and the nature and likelihood of their effect on outcomes that matter to patients. The synthesis of evidence should be comprehensive and up-to-date, and the evidence itself subject to critical appraisal. Ethical (informed patient choice), quality-of-care (patient-centered care), and scientific (evidence-based medicine) arguments justify this requirement. Empirical evidence suggests that over two thirds of available decision aids are based on high-quality evidence syntheses. Emerging issues identified include the duties of developers regarding the conduct of systematic reviews, the impact of comparative effectiveness research, their link with guidelines based on the same evidence, and how to present the developers’ confidence in the estimates to the end-users. Systematic application of the GRADE system, common in contemporary practice guideline development, could enhance satisfaction of this dimension. CONCLUSIONS: While theoretical and practical issues remained to be addressed, high-quality patient decision aids should adhere to this dimension requiring they be based on comprehensive and up-to-date summaries of critically appraised evidence.